Preferential Solvation of Mordant Black and Solochrome Dark Blue in Mixed Solvents Systems. (2019)
In this study, the preferential solvation of Mordant Black and Solochrome Dark Blue were investigated in mixed solvent systems of aqueous methanol, ethanol, propan-1-ol, propan-2-ol, methanol: ethanol, ethanol:propan-1-ol, methanol:propan-2-ol, ethanol:propan-1-ol, ethanol:propan-2-ol, propan-1-ol:propan-2-ol and carbon tetrachloride: dimethylformamide. Results showed a deviation of solvation data from ideality over the majority of composition ranges in all the solvent mixtures. The type and contribution of specific and non-specific solute-solvent interactions were analyzed in the framework of the linear solvation energy relationships. Statistical analysis of single, dual, and multiparametric equations revealed that in pure solvents, spectral behaviours of MB and SDB were affected by the polarity and basicity of the solvent milieu respectively. However in aqueous alcohols, polarity of the solvent milieu was the most significant determinant of spectral patterns with α and β parameters playing secondary contributory roles in the spectral changes of MB and SDB, respectively. Multiparametric equations generally yielded the best fitted model in mixed alcohol systems with polarity remaining the largest contributor, followed by β and α of the solvent milieu in that order. Spectral-structure relationships identified ion-dipole interactions involving the charged sulphonate and hydrazone moieties as well as protondonor-acceptor interactions of the common labile hydroxyl groups as mechanisms for the observed solvation data.